Innovation Through Heterochrony: An Amphioxus Perspective on Telencephalon Origin and Function - Lacalli, Thurston (Frontiers in Ecology and Evolution, 2021)
Heterochrony has played a key role in the evolution of invertebrate larval types, producing “head larvae” in diverse taxa, where anterior structures are accelerated and specialized at the expense of more caudal ones. For chordates, judging from amphioxus, the pattern has been more one of repeated acceleration of adult features so that they function earlier in development, thus converting the ancestral larva, whether it was a head larva or not, into something progressively more chordate-like. Recent molecular data on gene expression patterns in the anterior nerve cord of amphioxus point to a similar process being involved in the origin of the telencephalon. As vertebrates evolved, a combination of acceleration and increasing egg size appears here to have allowed the development of a structure that would originally have emerged only gradually in the post-embryonic phase of the life history to be compressed into embryogenesis. The question then is what, in functional terms, makes the telencephalon so important to the survival of post-embryonic ancestral vertebrates that this was adaptively advantageous. A better understanding of the function this brain region performs in amphioxus may help provide the answer.